Building a RefWorks Database of Faculty Publications as a Liaison and Collection Development Tool - Scott Marsalis; Julia Kelly (Issues in Science and Technology Librarianship, 2004)
Using RefWorks, a web-based citation manager, we constructed databases containing the publications of the faculty members for four departments on the St. Paul campus of the University of Minnesota. The goals were to learn more about the research interests in the departments and to have a tool to help inform us when trying to make decisions about book purchases and journal cancellations. A few unexpected challenges were encountered and a number of unexpected benefits emerged.